Geographical zoning of Russia - Vladimir Gorbanyov (European Regional Science Association (ERSA), 2014)
Russia has 11 economic regions - areas that differ from one another in their specialization, a special place in the geographical division of labor. However, the economic zoning of Russia, played a great role in the development of the economic potential of the USSR, largely out of date. Many regions were formed over 70 years ago, they did not contribute to the formation of new market structures, do not consider social and environmental features of the territory, and poor fit with natural boundaries. Federal districts also do not exactly correspond to any modern scientific criteria. So several different classification areas, taking into account both socio- economic and natural features of the area in terms of market reforms are suggested. Central region - historical, political, economic center of the country. It includes 27 subjects of the Russian Federation. North region actually coincides with the same area, which had existed previously . It consists of 5 subjects of the Federation. South region - the breadbasket of Russia, comprising 10 federal subjects. The North Caucasus region - the smallest and most multicultural area of Russia. Consists of 7 Federation subjects - 7 republics. Ural-Volga region - Russia 's oldest industrial area, linking the European and Asian parts of Russia, consists of 8 subjects of the Federation. Western Siberia region - an area of new development - the main oil-gas region of Russia, consisting of 8 subjects of the Federation. North Siberian region - also the area of new development, the main diamond mining area, consisting of five subjects of the Federation . South Siberian region - the most developed part of Siberia, gravitating to Transsibirian Railway; includes 8 of the Federation. Far Eastern region - yet it is the least developed regions, although thanks to a wide outlet to the Pacific Ocean, abundant natural resources contains great enormous potential. It consists of five subjects of the Federation. As a result, 9 natural-economic regions are proposed to allocate in Russia, which are accompanied by statistical data: area, population, natural and mechanical growth of population, gross regional product per capita, percentage of the population below the poverty line, the human development index, the structure employment.
Keywords: R1; 330; Russia; phisical geography; economics